Comparison of a Broad-Based Screen versus Disorder-Specific Screen in Detecting Young Children with an Autism Spectrum Disorder - Wiggins, Lisa D. (Autism, 2012)
The goals of our study were to (a) compare agreement between autism spectrum disorder diagnosis and outcome of the Modified Checklist for Autism in Toddlers and Parents Evaluation of Developmental Status in a sample of toddlers and (b) examine specific concerns noted for toddlers who screened negative on the Modified Checklist for Autism in Toddlers or Parents Evaluation of Developmental Status but were later diagnosed with autism spectrum disorder. Participants were administered the Modified Checklist for Autism in Toddlers and Parents Evaluation of Developmental Status during well-child visits. Families were invited for a clinical evaluation if autism spectrum disorder symptoms were noted on the Modified Checklist for Autism in Toddlers and Modified Checklist for Autism in Toddlers Follow-Up Interview or if autism spectrum disorder concerns were noted by the pediatrician. Fifty-two children completed the Modified Checklist for Autism in Toddlers, Parents Evaluation of Developmental Status, and a clinical evaluation, and 30 of these children were diagnosed with an autism spectrum disorder. Modified Checklist for Autism in Toddlers results showed higher agreement with autism spectrum disorder diagnosis than any individual Parents Evaluation of Developmental Status screen result, although the latter detected many children with other developmental concerns. Children who screened negative on the Modified Checklist for Autism in Toddlers or Parents Evaluation of Developmental Status but were diagnosed with autism spectrum disorder had concerns noted in sensory response and proto-declarative pointing that can be considered in the context of screen results. In sum, our findings support universal autism spectrum disorder–specific screening in addition to general developmental screening and offer considerations to encourage early identification of toddlers with autism spectrum disorder.